2016
DOI: 10.1016/j.bmc.2016.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of santacruzamate A analogues for anti-proliferative and immunomodulatory activity

Abstract: Santacruzamate A (SCA) is a natural product isolated from a Panamanian marine cyanobacterium, previously reported to have potent and selective histone deacetylase (HDAC) activity. To optimize the enzymatic and cellular activity, 40 SCA analogues were synthesized in a systematic exploration of the zinc-binding group (ZBG), cap terminus, and linker region. Two cap group analogues inhibited proliferation of MCF-7 breast cancer cells, with analogous increased degranulation of cytotoxic T cells (CTLs), while one ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 47 publications
1
20
1
Order By: Relevance
“…Analogs were categorized by their cap. It was found that the proliferation of MCF-7 breast cancer cells was inhibited in two group analogs and other analogs seemed to influence the degranulation of cytotoxic T-cells (121).…”
Section: N-(2-hydroxyphenyl)-2propylpentanamide N-(2-hydroxy-mentioning
confidence: 99%
“…Analogs were categorized by their cap. It was found that the proliferation of MCF-7 breast cancer cells was inhibited in two group analogs and other analogs seemed to influence the degranulation of cytotoxic T-cells (121).…”
Section: N-(2-hydroxyphenyl)-2propylpentanamide N-(2-hydroxy-mentioning
confidence: 99%
“…The general methods for the synthesis of O -thiocarbamates and dithiocarbamates traditionally rely on substitution reactions of the corresponding halogenated precursors, including thiophosgene [3133], thiocarbamoyl chlorides [3437], chlorothionoformates or chlorodithioformates [3841] providing the appropriate thiocarbamate analogues in good yields (Scheme 1). However, these methods suffer from the formation of toxic, malodorous and/or extremely corrosive byproducts generated by the elimination of the halogen atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Santacruzamate A (CAY10683) is a potent selective HDAC inhibitor that has an IC50 of 119 pM for HDAC2 and a >3600-fold selectivity over other HDACs [ 10 ]. As a clinically approved HDAC inhibitor, CAY10683 has antiproliferative and immunomodulatory effects [ 11 ], thereby CAY10683 was used to treat cutaneous T-cell lymphoma [ 12 ] and breast cancer [ 13 ].…”
Section: Introductionmentioning
confidence: 99%